Investigation of deep cryogenic treatment of Steels for medical tooling applications. Issue 1 (February 2021) - Biswas, P.; Ghosh, S.; Sarkar, A.; Roy, N.G.
Abstract: Hardened steels, which are resistant to corrosive chemical environments, are quite popular in the medical fields for various tooling applications exposed to low temperature. Using deep cryogenic treatments hardness and corrosion resistance of steel can be significantly improve for better compatibility of steels in biomedical applications. The present investigation examines the microstructure and evaluates hardness values of deep cryogenically heat treated AISI M2 steel. Studies on cryogenically treated tool steel show microstructural changes in the material can influence the life of the tools significantly. Through pertinent analyses of the experimental results this investigation infers that deep cryogenic treatment of AISI M2 steel increases the hardness of specimens marginally with the increase in the number of tempering cycle. The treatment further provides opportunity to exploit the possible use to hardened steels in robotic arms operative at low temperature research labs.